Knowledge and Attitudes Associated with Family Participation in Hallucinating Patient Care at Prof. Dr. Muhammad Ildrem Mental Hospital in 2022 - Dina Yusdiana D; Popy Herawati Damanik; Solihuddin Harahap; Wasal Desrial Siregar (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Hallucinations are sensory perception disturbances that occur in the absence of external stimuli and can affect any sensory system. They can occur when a person's consciousness is strong or full. People who have hallucinations frequently believe that their surroundings are the source or cause of their symptoms. The goal of this study was to determine how families' knowledge and attitudes related to the care of patients with hallucinations at the Prof. Mental Hospital. Muhammad Ildrem Medan, M.D. Year 2022. The research design employed cross-sectional methodology and analytical research. A total of 98 people were randomly selected from the study population, which included the patient's family. To collect data, questionnaires were distributed. In data analysis, the statistical test for Spearman's rank was used. According to the findings of the study, there is a significant relationship between knowledge, attitudes, and family involvement in treating hallucination sufferers. A descriptive analytic method with a cross sectional design, a total sample of 98 respondents, an accidental sampling strategy, and a total population of 8,893 respondents were used in this study. According to the study's findings, there was a relationship between family participation and hallucinatory patients with a 95% confidence level of 0.38 (0.05) and a relationship between family attitudes and family participation with a value of 0.19 (0.05). It is hoped that respondents will increase and strengthen their influence on hallucinatory subjects by providing assessment, instrumental, informational, and emotional support.